Protective Effect of Salidroside Against Diabetic Kidney Disease Through Inhibiting BIM-Mediated Apoptosis of Proximal Renal Tubular Cells in Rats - Guo, Congcong; Li, Yun; Zhang, Rui; Zhang, Yaqin; Zhao, Junyu; Yao, Jinming; Sun, Jie; Dong, Jianjun; Liao, Lin (Frontiers in Pharmacology, 2018)
Background: Accumulating evidences indicate that the apoptosis of proximal tubular epithelial cells (PTECs) play a vital role in the progression of the diabetic kidney disease (DKD). This study aimed to explore the therapeutic potential of salidroside (SAL) in DKD and its underlying mechanism in anti-apoptosis of PTECs. Methods: 28 male Wistar rats were allocated into four groups: sham-operated, uninephrectomy (unx), diabetes with uninephrectomy (DKD) and DKD treated with SAL (DKD+SAL). SAL (70 mg/kg) was gavage administered for 8 weeks. 24-h albuminuria and serum creatinine (SCr), blood urea nitrogen (BUN), renal histological changes were examined. The silico analysis was used to identify the main therapeutic targets and pathways of SAL involved in DKD treatment. Apoptosis was determined by TUNEL and Annexin V-FITC/PI double staining in vivo and in vitro, respectively. The expression of BIM, BAX and cleaved caspase-3 were evaluated by western blot and immunostaining. Results: Treatment with SAL significantly attenuated diabetic kidney injury via inhibiting 24-h albuminuria, SCr, BUN, glomerular mesangial dilatation and tubular injury in DKD rats. The silico analysis identified the intrinsic apoptotic pathway as an important pathway responsible for the nephroprotective properties of SAL. Our data validated that SAL effectively inhibited the apoptosis of PTECs induced by high-glucose (HG), both in vitro and in vivo. Silence of BIM by shRNA in HK-2 cells prevented HG-induced apoptosis. The up-regulated BIM and its downstream targets (BAX, and cleaved caspase-3) were also inhibited by SAL. Conclusion: In summary, SAL significantly relieved DKD. And the possible mechanisms might be partially attributed to inhibiting apoptosis of proximal renal tubular cells. The apoptotic protein BIM could be an important target of SAL in this process.